Redesain Proses Verifikasi Dokumen Pembayaran Dalam Transisi Digital SIG - Mohammad Khoirul Huda; Bambang Tutuko; Gatot Kustyadji (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study examines the redesign of payment document verification processes during the 2021–2025 digital transition period at SIG. The study is motivated by the fact that digitalization in financial administration does not merely replace paper documents with electronic files, but also changes approval flows, evidence standards, archival mechanisms, and internal control points. This research applies a descriptive qualitative method with a single case study approach. Data were collected through semi-structured interviews concerning process developments during 2021–2025 and document analysis. The 2019 payment verification procedure was used as a pre-period baseline, while the 2026 procedure was used only as post-period documentary confirmation of the process configurations identified from the interviews. The data were analyzed through thematic coding, process mapping, and source triangulation. The findings show that the transformation resulted in four process configurations: paperless processes based on scanned original evidence, structured paperless processes supported by SAP/e-invoice/e-sign/e-meterai, hybrid processes using system submission and hardcopy matching, and manual processes retained for transaction evidence that cannot yet be standardized digitally. The study finds that process redesign is shaped by evidence controllability, system readiness, legal validity, and risk control needs. The contribution of this study is to provide an empirical reading of digital transformation as a differentiated process redesign, rather than a uniform migration from manual documents to digital systems.